Millennial Generation Perceptions’ on Cash Waqf Donations (Case Study of the Millennial Generation at Malang Raya) - Hakim, Rahmad; Hakim, Arif Lukman (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
This study explores the perceptions and attitudes of the Millennial generation toward cash waqf donations in Malang Raya, Indonesia. As a contemporary Islamic philanthropic instrument, cash waqf holds significant potential for economic empowerment and social development. However, its utilization among younger generations remains relatively underexplored. Using a mixed-method approach, this research combines quantitative survey data from 136 millennial respondents with qualitative insights gathered through in-depth interviews. The findings reveal a moderate level of awareness and understanding of cash waqf among Millennials, with digital accessibility, religious motivation, and perceived social impact serving as key influencing factors in their willingness to donate. Furthermore, trust in waqf institutions and the transparency of fund management emerged as critical components shaping their engagement. This study provides valuable insights for waqf institutions, policymakers, and Islamic financial developers to design targeted strategies that resonate with the values and digital behavior of the Millennial demographic.